KEDUDUKAN KEPALA DESA SEBAGAI HAKIM PERDAMAIAN - Samuel Dharma Putra Nainggolan (Universitas Bengkulu, 2018)
The rural population is a basic capital for national development, owned by the people and the Indonesian nation. In the constitutional structure of the Republic of Indonesia, the Village has developed in various forms and is obliged to be protected and empowered to be strong, advanced, and democratic and democratic so as to carry out governance and development towards a just, prosperous and prosperous society. The involvement of the Village Head in resolving conflicts within rural communities has made the writer interested in studying the nature of cases out of court settlement by the Village Head against the village community and the reformulation of legal policies in implementing the nature of the settlement of a non-court problem. The approach used in this research is statute approach, historical approach, and conceptual approach, and case approach. The results of this study states that solving a problem that occurs in the village by placing the Village Head as a peace judge is a form of discretion / policy of the executive in order to realize public service for the community. In other words because it is a discretion, it certainly follows the laws and regulations that state the limits of it.